1970
DOI: 10.1111/j.1440-169x.1970.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Perithecial Formation in Gelasinospora Reticulispora. I. Effects of Light at Two Different Growth States

Abstract: Hyphae of Geiasinospora reiicutispora were cultured on corn meal agar m a growth tube at 25 k 0.4"C under different light conditions. While the hyphal tip was growing, perithecia were not formed under continuous white light (ca. 2000 ergs cm-2 sec-'), but some perithecia were initiated in total darkness. However, when white light was given after a dark period, perithecial formation was greatly promoted. In these cases, perithecial formation occurred in older portion of the culture (the portion nearest the poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Apparently, a minute quantity of light in March (one lux or less) is sufficient to induce formation of tiny fruit bodies in G. esculenta (see Inoue & Furuya 1970). The discovery of a mycochrome in this species might make it possible to develop techniques· for the cultivation of the fungus.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, a minute quantity of light in March (one lux or less) is sufficient to induce formation of tiny fruit bodies in G. esculenta (see Inoue & Furuya 1970). The discovery of a mycochrome in this species might make it possible to develop techniques· for the cultivation of the fungus.…”
Section: Discussionmentioning
confidence: 99%
“…Ascocarps formed under this condition, therefore, should be called perithecia. Ascocarps induced by aging under continuous white light : Although it was reported that no visible ascocarp occurred in cultures placed under continuous white light for 7 days (Inoue and Furuya, 1970), ascocarps were formed in the cultures even under continuous white light when incubated for a longer period of time. Ascocarp development took place very similarly to that just described, except for about 2 days of retardation, counted from the inoculation.…”
Section: Resultsmentioning
confidence: 99%
“…84 a single ascospore. Culture procedures and light sources were previously described (Inoue and Furuya, 1970). Samples were obtained as an agar block (about 1 cm long x 1 cm in width x 3 mm in depth) from the region of the growth tube where the earliest ascocarps had appeared.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation